Expression dynamics of phytochrome genes for the shade-avoidance response in densely direct-seeding rice - Cui, Yongtao; Zhu, Minhua; Song, Jian; Fan, Honghuan; Xu, Xiaozheng; Wu, Jiayan; Guo, Longbiao; Wang, Jianjun (Frontiers in Plant Science, 2023)
Because of labor shortages or resource scarcity, direct seeding is the preferred method for rice (Oryza sativa. L) cultivation, and it necessitates direct seeding at the current density. In this study, two density of direct seeding with high and normal density were selected to identify the genes involved in shade-avoidance syndrome. Phenotypic and gene expression analysis showed that densely direct seeding (DDS) causes a set of acclimation responses that either induce shade avoidance or toleration. When compared to normal direct seeding (NDS), plants cultivated by DDS exhibit constitutive shade-avoidance syndrome (SAS), in which the accompanying solar radiation drops rapidly from the middle leaf to the base leaf during flowering. Simulation of shade causes rapid reduction in phytochrome gene expression, changes in the expression of multiple miR156 or miR172 genes and photoperiod-related genes, all of which leads to early flowering and alterations in the plant architecture. Furthermore, DDS causes senescence by downregulating the expression of chloroplast synthesis-related genes throughout almost the entire stage. Our findings revealed that DDS is linked to SAS, which can be employed to breed density-tolerant rice varieties more easily and widely.